Effect of vitamins, protein level and probiotics on immune response of moulted male broiler breeders. Issue 4 (20th June 2013) - Khan, R. U.; Rahman, Z. U.; Javed, I.; Muhammad, F.
Summary This study was planned to investigate the comparative effect of vitamins C (L‐ascorbic acid), E (DL‐α‐tocopherol acetate), probiotics, lower than normal protein level (14%) and combination of these treatments on immune response of male broiler breeders after zinc‐induced moulting. One hundred and eighty birds at the age of 65 weeks were induced to moult by mixing zinc oxide (ZnO) in feed at the rate 3000 IU/kg of feed. Upon completion of moulting, birds were divided into six groups (five replicates per group) in a completely randomized design and were fed vitamin C (500 IU/kg), vitamin E (100 IU/kg), lower protein level, probiotics (50 mg/l), and a combination of these components, while one group was kept as control. After completion of moulting phase (5 weeks), the treatment effects were tested as in vitro macrophages engulfment percentage, nitric oxide (NO) production, serum antibody titres against Newcastle disease (ND) and infectious bronchitis (IB). The results showed that in vitro macrophage engulfment percentage in unopsonized conditions was significantly higher in vitamin E‐supplemented group. In addition, in opsonized condition, the macrophage engulfment percentage was significantly higher in both vitamin E‐ and C‐supplemented groups. The NO (opsonized and unopsonized) production and antibody titre against ND and IB were significantly higher in vitamin E‐supplemented group. It was concluded that vitamin E is a better option for enhanced immune response in broiler breeders after zinc‐induced moulting.